2010
DOI: 10.1111/j.1476-5381.2010.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of systemic inhibition of Rho kinase on blood pressure and renal haemodynamics in diabetic rats

Abstract: BACKGROUND AND PURPOSE The RhoA/Rho associated kinases (ROCK) pathway has been implicated in the pathophysiology of diabetic nephropathy (DN). Early stages of diabetes are associated with renal haemodynamic changes, contributing to later development of DN. However, the role of RhoA/ROCK, known regulators of vascular tone, in this process has not been studied.EXPERIMENTAL APPROACH Blood pressure (BP), glomerular filtration (GFR), effective renal plasma flow and filtration fraction (FF) in response to the ROCK i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 51 publications
3
26
1
Order By: Relevance
“…The contractile and MLC phosphorylation responses to cirazoline of caudal artery strips isolated from type 2 diabetic Goto-Kakizaki rats were significantly reduced compared to those of age-matched Wistar rats [14]. Vehicle-treated diabetic rats demonstrated increased renal MLC phosphorylation as compared to the control animals [15]. Phosphorylation of MLC in the smooth muscle of coronary microvessels was significantly increased in the diabetic Yucatan miniswine compared with the controls [16].…”
Section: Discussionmentioning
confidence: 95%
“…The contractile and MLC phosphorylation responses to cirazoline of caudal artery strips isolated from type 2 diabetic Goto-Kakizaki rats were significantly reduced compared to those of age-matched Wistar rats [14]. Vehicle-treated diabetic rats demonstrated increased renal MLC phosphorylation as compared to the control animals [15]. Phosphorylation of MLC in the smooth muscle of coronary microvessels was significantly increased in the diabetic Yucatan miniswine compared with the controls [16].…”
Section: Discussionmentioning
confidence: 95%
“…Berberine exerts renoprotective effects on experimental diabetic models closely associated with glucose and lipid metabolism, antioxidative stress, and anti-inflammation by downregulating the NF-κB, RhoA/ROCK, and SphK1-S1P pathways [18,19]. However, the possible mechanisms have not been fully established.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, BBR exhibits antioxidant activity and improves insulin resistance and hemodynamics [16,17]. In an experimental diabetic kidney model and high glucose-cultured GMCs, BBR represses the expression of FN, ICAM-1, and TGF-β1 possibly by negatively regulating NF-κB and RhoA/ROCK [18,19]. Furthermore, BBR ameliorates DN by inhibiting the Sphk1/S1P signaling pathway and MAPK activation, lowering AP-1 activity, and eventually deceasing fibronectin overproduction [20][21][22].…”
Section: Introductionmentioning
confidence: 91%
“…Although there was a trend towards decreased blood pressure in the middle-dose fasudil group, this trend was not significant. Komers et al reported that acute administration of fasudil decreased blood pressure in both control and diabetic rats [28] . However, hypertension is the most common adverse event associated with VEGFR-tyrosine kinase inhibitors, and ROCK inhibition blunts sunitinib(VEGF antagonist) -induced hypertension [29] .…”
Section: Discussionmentioning
confidence: 99%